Passura Tongkonan Toraja and Community Work Ethic in Rantepao Subdistrict, North Toraja Regency - P, Efendi; Sabaruddin, Sabaruddin; Kasmi, Kasmi; Saldin, Muh; Amiruddin, Idris (Universitas Andalas, 2024)
The study describes the traditional traditions of the Toraja land community which explains that Passura' carvings in the Toraja ethnic community are known as a philosophy of life and ancestral heritage which plays an important role in depicting social norms and conveying philosophical messages. The four basic Toraja carvings from more than 150 types of carvings, called Garonto Passura', such as Pa' Barre Allo, Pa' Tedong, Pa'manuk Londong, and Pa' Sussu, have special meanings involving important symbols. Garonto Passura' reflects values such as prosperity, hard work, justice, knowledge, nobility and unity of Toraja society. Each carving has a specific meaning, imbued with the values of Toraja life such as honesty, hard work, cooperation and unity. Tongkonan carvings, especially Pa' Tedong, Pa'manuk Londong, Pa' Barre Allo, and Pa' Sussu, not only reflect high artistic aesthetic values, but are also an important forum for conveying cultural messages, norms and values. which strengthens the work ethic of the Torajan people as a whole, enabling them to maintain traditions and apply ancestral values in everyday life. The work ethic of the Toraja people, reflected in Tongkonan carvings, teaches the importance of honesty, determination, hard work, cooperation and unity as the keys to prosperity and success in life.